An ESTRO-ACROP guideline on quality assurance and medical physics commissioning of online MRI guided radiotherapy systems based on a consensus expert opinion. (April 2023) - Tanadini-Lang, Stephanie; Budgell, Geoff; Bohoudi, Omar; Corradini, Stefanie; Cusumano, Davide; Güngör, Görkem; Kerkmeijer, Linda G.W.; Mahmood, Faisal; Nill, Simeon; Palacios, Miguel A.; Reiner, Michael; Thorwarth, Daniela; et al.
Highlights: A consensus guideline on quality assurance and medical physics commissioning of online MRI guided radiotherapy systems applicable to all commercially available systems. Quality assurance tests during commissioning and routine QA were identified. Medical Physics aspects during commissioning such as constructions issues, teaching and emergency procedures are summarized and discussed. Abstract: Objective: The goal of this consensus expert opinion was to define quality assurance (QA) tests for online magnetic resonance image (MRI) guided radiotherapy (oMRgRT) systems and to define the important medical physics aspects for installation and commissioning of an oMRgRT system. Materials and Methods: Ten medical physicists and two radiation oncologists experienced in oMRgRT participated in the survey. In the first round of the consensus expert opinion, ideas on QA and commissioning were collected. Only tests and aspects different from commissioning of a CT guided radiotherapy (RT) system were considered. In the following two rounds all twelve participants voted on the importance of the QA tests, their recommended frequency and their suitability for the two oMRgRT systems approved for clinical use as well as on the importance of the aspects to consider during medical physics commissioning. Results: Twenty-four QA tests were identified which are potentially important during commissioning and routine QA on oMRgRT systems compared to online CT guided RT systems. An additional eleven tasks and aspects related to construction, workflow development and training were collected. Consensus was found for most tests on their importance, their recommended frequency and their suitability for the two approved systems. In addition, eight aspects mostly related to the definition of workflows were also found to be important during commissioning. Conclusions: A program for QA and commissioning of oMRgRT systems was developed to support medical physicists to prepare for safe handling of such systems.